The role of Interleukin-12 in immune-mediated rheumatic diseases - A. Spadaro; R. Scrivo; T. Rinaldi; V. Riccieri; A. Sili Scavalli; E. Taccari; G. Valesini (PAGEPress Publications, 2002)
Objective: IL-12 is a proinflammatory cytokine produced by different antigen presenting cells. It has been shown to exert a critical role in inducing Th1 phenotype, thus initiating cell-mediated immune responses, but the significance of IL-12 in rheumatic diseases is not clear. Aim of the study was to determine IL-12 serum levels in immune rheumatic diseases and to analyse the relationship of this cytokine with main clinical and laboratory parameters. Methods: we analysed, by ELISA, serum IL-12 levels in 114 patients with SLE, 47 with SS, 32 with SSc, 84 with RA, 138 with PA and in 17 healthy controls. We also examined main clinical and laboratory parameters, including autoantibody profile and clinical indices of disease activity. Results: IL-12 serum levels were significantly higher in SLE and SS patients respect to controls. IL-12 serum levels were significantly higher in SLE patients compared to those affected by RA, PA and SSc. When we evaluated disease activity in SLE patients, we found significantly higher IL-12 serum levels in subjects with fever or in those without renal involvement, while no correlation was found in the other rheumatic immune diseases. Conclusions: these findings suggest that IL-12, modulating cell and humoral immune responses, is involved in the pathogenesis of immune rheumatic diseases, such as SLE and SS.